Test of Water Hyacinth Bokashi and Plant Growth Regulator on Black Rice Plants - A. Asrijal; R. Rahmawati; Ambo Upe (Agrotech Journal, 2022)
Water hyacinth is a type of plant that grows in freshwater environments. This plant is an ideal raw material to produce bokashi which increases the availability of soil nutrients. To maximize the function of the water hyacinth bokashi, a growth regulator is used to encourage plant upatake of soil nutrients. This study aimed to examine the single effect and interaction between water hyacinth bokashi (BHW) and plant growth regulators (PGR) on black rice. Data were analyzed with a factorial randomized block design. The first factor is WHB (B) 0 ha-1 and 2 t ha-1, while the second factor is PGR (Z) 0 ppm and 1.5 ppm. The results showed that the best effect of grain weight per hectare was treatment with WHB 2 t ha-1, PGR 1.5 ppm, and their interactions were 10.34 t ha-1; 11.09 t ha-1, and 12.16 t ha-1 harvested dry rice